Waqf financing, investment and development of higher educational institutions: A study of Pakistan and Malaysia / Muhammad Usman - Muhammad , Usman (2019)
This research studies waqf financing, investment, and development of Higher Educational Institutions (HEIs) in Pakistan and Malaysia and compares them. The study also discusses issues and challenges in waqf development in both countries. In this context, the present qualitative study adopting a case method through interpretivism research paradigm and selected three case studies from each country. To look upon, the study conducted in-depth (open-ended) interviews with key personnel of higher educational waqf institutions including waqf mutawallis, administrators, directors, and managers. In addition, the legal and sharī’ah experts’ opinions are also incorporated in the study. To ensure the comprehensive results, the study converges data sources through triangulation. The findings of the study revealed that the waqf has a significant contribution to higher education institutions development in both countries. In Pakistan, both public and private awqāf are operational but the role of private awqāf is greater. In this scenario, Pakistan’s waqf institutions are more developed and since have diversification in fundraising, fund-management, and fund utilisation. While in Malaysia the waqf institutions are centralized and controlled by the religious councils Majlis Agama Islam Negeri (MAIN) of each state. The study also finds that an efficient waqf institution not only has the ability to assist higher education, but it can also strengthen the economic growth of the country. While it has not been used in full potential so, there is an extra room to use it for higher education development. For these reasons, it is the responsibility of both governments to assist waqf through creating greater understanding and introducing legislation for a feasible environment for waqf practices in higher education development as a third sector. Further based on the findings the study suggested some policy implications that might help policymakers, fundraisers, fund managers, legislators, and mutawallis’of waqf institutions.